MOBILE LIBRARY APPLICATION MODELING FOR STRENGTHENING DIGITAL-BASED STUDENT'S READING WRITING INTEREST - Suhardi, Suhardi (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Digital literacy is very important at this time. Proficiency in using technology is a must in order to compete nationally and internationally. One way to improve literacy patterns is to obtain a lot of information and reading materials through the library. Technological devel-opments make libraries have to innovate so that conventional libraries become digital li-braries. At the library of the State Islamic University of North Sumatra (UINSU) Medan itself, the literacy pattern has utilized the digital library. It just needs better innovation by creating responsive mobile applications. This application model will focus on providing digital books so that they can be accessed from anywhere without having to visit the li-brary. The development of this application model uses the Research and Development (R&D) method and is designed using the UML model and with various tools and various programming languages such as Android Studio, HTML, CSS, and PHP which will later produce a responsive web view. There are 3 access rights in the mobile library application, namely Administrators, Library Members and Library Visitors who have their own access rights. This application model runs well on the android platform which is relevant to today and makes it easy for users because it can be accessed anywhere and anytime and has online reading, borrowing and returning features.